Defining social entrepreneurship = Eine Definition von Social Entrepreneurship - Jansen, Stephan A.; Richter, Saskia; Hahnke, Elisabeth; Achleitner, Ann-Kristin; Spiess-Knafl, Wolfgang; Volk, Sarah; Then, Volker; Mildenberger, Georg; Scheuerle, Thomas; Schmitz, Björn (Social Science Research Network, 2011)
The Mercator Research Network Zeppelin University - TU Munich - CSI Heidelberg analyzes the organization, communication, legitimacy and governance of social entrepreneurs. The underlying definition uses fourteen criteria to characterize social entrepreneurship and tries to differentiate between different phenomena.
Gesehen am 19.11.2019